Consistency or contradiction? Mobility- Related Attitudes and Travel Mode Use of the Young ‘New Generation’. - Konrad, Kathrin; Groth, Sören (de Gruyter Poland - Sciendo, 2020)
In this paper, we examine the role of mobility-related attitudes in the travel mode use of young people, the extent to which young adults and teenagers behave consistently in relation to their attitudes, and the conditions on which the consistency of attitudes and behaviour depends. We thus continue the current discussion about the loss of importance of the car for young people in which various socio-demographic trends, but also changed attitudes, are used as explanatory factors, especially on a hypothetical level. Our contribution closes a research gap in that so far neither the relationship between attitudes and behaviour among young people has been empirically investigated nor has this relationship been empirically placed in a context of spatial, economic and socio-demographic conditions. We address this by means of differentiated correlation analyses and the calculation of correlation differences on the basis of a nationwide German survey of young people from 2013. This enables us to demonstrate that young people basically behave consistently in line with their attitudes. However, there are significant differences which confirm that certain spatial, economic and socio-demographic conditions are essential for the implementation of attitudes into corresponding travel mode use.

In diesem Beitrag setzen wir uns mit folgenden Fragen auseinander: Welche Rolle spielen mobilitätsbezogene Einstellungen bei der Verkehrsmittelnutzung junger Menschen? Inwiefern verhalten sich junge Erwachsene und Jugendliche konsequent in Bezug auf ihre verkehrsmittelbezogenen Einstellungen? Von welchen Voraussetzungen und Rahmenbedingungen hängt eine Konsistenz von Einstellungen und Verhalten ab? Wir knüpfen damit an die aktuelle Diskussion um den Bedeutungsverlust des Autos für junge Menschen an, in der soziodemographische Trends, aber auch veränderte Einstellungen vor allem auf hypothetischer Ebene zur Erklärung herangezogen werden. Unser Beitrag schließt eine Lücke: Bislang wurde weder der Zusammenhang zwischen Einstellungen und Verhalten bei jungen Menschen empirisch untersucht, noch wurde dieser Zusammenhang empirisch in einen Kontext räumlicher, ökonomischer und soziodemographischer Rahmenbedingungen eingeordnet. Wir analysieren dies mittels differenzierter Korrelationsanalysen und der Berechnung von Korrelationsunterschieden anhand einer deutschlandweiten Befragung Jugendlicher und junger Erwachsener aus dem Jahre 2013. Damit können wir nachweisen, dass sich junge Menschen prinzipiell konsequent gemäß ihren Einstellungen verhalten. Dabei gibt es aber signifikante Unterschiede, die bestätigen, dass räumliche, ökonomische und soziodemographische Rahmenbedingungen dafür wesentlich sind.
Keywords: Verkehrsforschung; Mobilitätsverhalten; Junger Erwachsener; Automobil; Einstellung; Verkehrsmittelnutzung; Häufigkeit; Verkehrsmittelwahl; Fahrrad; ÖPNV; PKW; Einflussfaktor; Stadtgröße; Lebenslage; Einkommenshöhe; Befragung